2018
DOI: 10.1002/gj.3399
|View full text |Cite
|
Sign up to set email alerts
|

Early Cretaceous arc granitoids from the central Lhasa subterrane: Production of the northward subduction of Yarlung Zangbo Neo‐Tethyan Ocean?

Abstract: There is ongoing debate as to the genesis of the Lhasa Terrane during the Mesozoic (northward subduction of Yanglu‐Zangbo Tethyan Ocean [YZTO] or southward subduction of Bangong–Nujiang Tethyan Ocean [BNTO]). In this paper, we report a dataset of geochronology, geochemistry, and Sr–Nd–Hf isotopes for the Azhale granitoids in order to elucidate the dominant geodynamic processes of the central subterrane. These rocks are dated at 142.2 ± 1.0 and 136.6 ± 0.6 Ma by zircon LA–ICP–MS method, indicating that these ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…However, the samples showed low Sr/Y and relatively high La/Yb, indicating that the melt was forming in the plagioclase stability field, with residues of garnet and plagioclase (Figures 3E,F), similar to those documented in Jurassic (160 Ma) Maofengshan (South China Block) metasedimentary-derived highly fractionated S-type granites that originated in the middle crust (16.5-20 km) (Liu X. et al, 2021). The chondrite-normalized and spidergram patterns showed that our samples were slightly evolved compared to those reported by Li R. H. et al (2019) from the Taxkorgan region. The exception was sample Psh-1 which displayed an identical pattern to those for the Taxkorgan granites (Figures 6A,B).…”
Section: Granitesupporting
confidence: 85%
See 1 more Smart Citation
“…However, the samples showed low Sr/Y and relatively high La/Yb, indicating that the melt was forming in the plagioclase stability field, with residues of garnet and plagioclase (Figures 3E,F), similar to those documented in Jurassic (160 Ma) Maofengshan (South China Block) metasedimentary-derived highly fractionated S-type granites that originated in the middle crust (16.5-20 km) (Liu X. et al, 2021). The chondrite-normalized and spidergram patterns showed that our samples were slightly evolved compared to those reported by Li R. H. et al (2019) from the Taxkorgan region. The exception was sample Psh-1 which displayed an identical pattern to those for the Taxkorgan granites (Figures 6A,B).…”
Section: Granitesupporting
confidence: 85%
“…This ambiguity is controlled by the entrainment of xenocrystic/or peritectic and accessory minerals and their constituent element concentrations in the melt. In combination with our data, we used the data from 118 Ma granitoids reported by Li R. H. et al (2019) (from the Taxkorgan region (Figure 1)), which plotted in the same fields as our samples (Figure 7D). Garnet containing elements such as Zr, Ce, Ga, Y, and others can be concentrated within refractory minerals such as zircon (Zr, Hf, Y, and Yb) and monazite (Ce and La) (Villaros et al, 2009b).…”
Section: Granitementioning
confidence: 99%
“…Granitoids have been used to investigate the formation and evolution of continental crust, and a large number of granitoids in a specific tectonic domain can provide petrological clues to deep crustal compositions and processes of crustal evolution (e. g., H. Zheng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The central Lhasa Terrane contains granitoids of various ages, and these granitoids provide clues regarding the composition of the crust and mantle and the nature of tectonic-magmatic events during India-Asia collision (Cao et al, 2019;Chung et al, 2005;Dai et al, 2020;Sheng et al, 2019;H. Zheng et al, 2018;Zhu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies were carried out on the southern Lhasa block (i.e., Jurassic to Cretaceous magmatism) which suggest an archetype of Andean‐style margin related to the northward subduction of the Neo‐Tethyan Ocean before the India–Asia collision in the Early Cenozoic (Chu et al, 2006; Chung, Chu, Zhang, et al, 2005; Ding, Kapp, Zhong, et al, 2003; Ji, Wu, Chung, Li, & Liu, 2009; Mo et al, 2007; Mo, Niu, Dong, et al, 2008; Yin & Harrison, 2000; Zhang et al, 2012; Zhou et al, 2018). However, the petrogenesis and tectonic settings of the Cretaceous magmatism in the central‐northern Lhasa block remain equivocal, with diverse models including the northward subduction of the Neo‐Tethyan Ocean lithosphere (Ma & Yue, 2010; Zhang et al, 2012; Zheng, Huang, Cai, et al, 2019), the southward subduction of the Bangong–Nujiang Ocean (Meso‐Tethyan Ocean) lithosphere and subsequent Lhasa–Qiangtang collision (Li et al, 2018; Mo et al, 2005; Pan, Mo, Hou, et al, 2006; Zhu et al, 2013; Zhu, Mo, Niu, et al, 2009a). Recently, delamination of a thickened lithospheric keel (including lithospheric mantle and lowermost crust) has also been proposed to account for the Late Cretaceous magmatism within the Lhasa–Qiangtang collision zone (Cao, Zhang, Santosh, et al, 2019; Chen et al, 2015; Wang, Tang, Wang, et al, 2019; Wang, Zhu, Zhao, et al, 2014; Yi et al, 2018; Yu, Chen, Xu, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%